PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA POKOK (Studi Kasus Penentuan Besarnya Tarif Jasa Rawat Inap Pada RSUD Deli Serdang Lubuk Pakam ) - SHITA TIARA; SYARIFAH LIDYA HADINI (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Activity Based Costing System is an accounting information system that implements the concepts of accounting activity to produce more accurate cost. Activity-based cost calculation is costing approach that charge resources to cost objects such as products, services, or customer based activities undertaken for the cost objects. Deli Serdang Hospital in determining the basic price is still using the traditional cost accounting. This system is not suitable for the calculation of the cost of products such as hospitals that have diversified (diversity) high product thus providing cost information is distorted. Determination of the basic price no longer reflects the specific activity because of the many categories of indirect and likely to remain (fixed). The results showed that there are differences in the magnitude of the cost in the determination of the rates of hospitalization services with traditional methods and Activity Based Costing System. Compared with traditional methods, Activity Based Costing System provides greater results. This happens because the loading overhead on each product is charged on many cost driver, so that the application of Activity Based Costing System has been able to allocate costs to each room activity hospitalization appropriately based on the consumption of each activity.